2020
DOI: 10.4103/ams.ams_187_19
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood pressure and pulse rate of patients without systemic diseases following the injection of 2% lidocaine plus epinephrine 1:80000 in an inferior alveolar nerve block - A prospective study

Abstract: Introduction: An inferior alveolar nerve block is dental anesthesia produced by the local injection of lidocaine plus epinephrine; however, its administration could cause cardiovascular side effects. We aimed to assess the changes in blood pressure and pulse rate following the injection of 2% lidocaine with epinephrine 1:80000 for an inferior alveolar nerve block. Materials and Methods: Seventy-one patients without any systemic disease were enrolled in this study. Systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Whether local anesthesia with adrenaline caused a change in blood pressure and heart rate during oral surgery, or whether it was the result of psychological stress due to oral surgery, was the subject of discussion by many authors 33,34 . A usual dose of epinephrine leads to a single increase in serum epinephrine concentration [33][34][35][36] . Furthermore, pain caused by the application of the injection was associated with an increase in the cardiovascular response 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether local anesthesia with adrenaline caused a change in blood pressure and heart rate during oral surgery, or whether it was the result of psychological stress due to oral surgery, was the subject of discussion by many authors 33,34 . A usual dose of epinephrine leads to a single increase in serum epinephrine concentration [33][34][35][36] . Furthermore, pain caused by the application of the injection was associated with an increase in the cardiovascular response 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing 0.5% and 0.75% ropivacaine for inferior alveolar nerve block in lower third molar surgery showed that 0.75% ropivacaine was more efficacious and desirable [ 5 ]. A 2% lignocaine hydrochloride with adrenaline (1:80,000) is safe for hemodynamically healthy patients [ 6 ]. In addition, 2% lignocaine with 1:80000 adrenaline is a commonly used anesthetic solution in dentistry.…”
Section: Introductionmentioning
confidence: 99%